Clarice Lispector, leitora de Graciliano Ramos? - Oliveira, Adriane Camara de (2007)
The main topic of this Dissertation consists in a comparison bewteen two important works of Brazilian literature, namely, Vidas secas and A hora da estrela. The comparison is grounded upon the fact that both works deal with the condition of the migrant in Brazil. In Vidas secas the topic is the displacment itself, due to poor conditions in the Sertão. In A hora da estrela seems to be more concerned with the consequences of this displacement through a character who already is within the context of a metropolis. In this Dissertation the following hypothesis will be developed: the displacement towards the urban centres, announced in Vidas secas comes to an end; it is as if the last paragraph of Graciliano Ramos novel is surprisingly rewritten in Clarice Lispector s prose in a nutshell, this is the aim of this Dissertation.